The effect of fasting or calorie restriction on mitophagy induction: a literature review. Issue 6 (27th August 2020) - Mehrabani, Sanaz; Bagherniya, Mohammad; Askari, Gholamreza; Read, Morgayn I.; Sahebkar, Amirhossein
Abstract: Mitochondrial dysfunction can be a major cause of a wide range of age‐related diseases. Maintaining the normal homeostasis of mitochondria population plays an important role in ensuring people's health, which is done through the mitophagy process. Among the various stimuli for the onset of mitophagy, caloric restriction (CR) is one of the strongest non‐genetic triggers for initiating the mitophagy process. The primary objective of this paper is to review the literature assessing the effect of CR on mitophagy. Medline, Web of Science, Scopus, and Google Scholar databases was searched from inception to 1 August 2019. Reference lists from all selected articles were also examined for additional relevant studies. The evidence regarding the effect of fasting or CR on mitophagy is still limited. In addition, the methodological approaches of the studies are too heterogeneous in terms of types of food restriction, study duration, and targeted tissues. Most of the studies showed that fasting or CR induced mitophagy and mitophagy‐related markers such as Binp3 and Parkin. However, some studies demonstrated that mitophagy occurred both in fasting and fed state with no significant differences or may be induced in fed state. Study on the muscle tissue of subjects after exercise showed that mitophagy was upregulated in the fed state. It has been demonstrated that mitophagy in the muscle was lowered in the absence of AMP‐dependent kinase and fibroblast growth factor 21 genes, both in fasted and fed conditions. Current evidence overwhelmingly suggests that CR and fasting induce mitophagy and mitophagy‐related markers. Based on the current evidence that we reviewed here, it could be concluded that fasting or CR has a promising role as a novel and practical approach in the prevention of age‐related diseases without any side effects by inducing mitophagy in different organs of the body. More studies will be required in future to clarify the relationship between food deprivation and mitophagy. Further studies using a variety of different types of CR and fasting states are also warranted to determine the best approach for inducing mitophagy and improving health.